Pengaruh Financial Knowledge Dan Financial Literacy Terhadap Financial Management Behavior Selama Pandemi Covid-19 - Asih Masita; Ronny Malavia Mardani; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of financial knowledge and financial literacy on financial management behavior in UMKM RPMR. This study used a purposive sampling technique which was carried out on 82 samples from 450 populations of UMKM RPMR members. The method used is a questionnaire. The data analysis technique uses descriptive test, instrument test (validity and reliability test), normality test, classical assumption test (multicollinearity and heteroscedasticity test), multiple linear regression analysis, statistical testing (t test) and the coefficient of determination test data processing using SPSS. The results of the study indicate that simultaneously there is an influence of financial knowledge and financial literacy on financial management behavior in UMKM RPMR. Keywords:financial knowledge, financial literacy, financial management behavior.